1998
DOI: 10.2165/00003495-199856040-00001
|View full text |Cite
|
Sign up to set email alerts
|

Are There Potential Non???Lipid-Lowering Uses of Statins?

Abstract: Recent clinical trials have demonstrated beyond doubt that statins are effective in the prevention of acute coronary events. Critical analysis of these studies suggests that the benefits of statin therapy cannot be fully explained on the basis of reductions in plasma cholesterol levels. Accumulating knowledge of the actions of these drugs shows that they may prevent several processes that eventually lead to plaque rupture and the development of occlusive thrombosis, the basis of acute coronary events. Hence, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 47 publications
1
24
0
2
Order By: Relevance
“…Following the same logic, it should not be concluded that if for a certain group the association of hyperlipidemia with poor survival is found in observational studies, then only that group would benefit from lipid-lowering interventions. Studies to identify unique characteristics of distinct sub-populations of MHD patients and patients with CHF and more clinical trials on the effect of cholesterol-lowering interventions on CKD survival (50,51) are urgently needed.…”
Section: Perspectivementioning
confidence: 99%
“…Following the same logic, it should not be concluded that if for a certain group the association of hyperlipidemia with poor survival is found in observational studies, then only that group would benefit from lipid-lowering interventions. Studies to identify unique characteristics of distinct sub-populations of MHD patients and patients with CHF and more clinical trials on the effect of cholesterol-lowering interventions on CKD survival (50,51) are urgently needed.…”
Section: Perspectivementioning
confidence: 99%
“…These benefits appear to derive largely from a stabilizing effect on vulnerable plaques through modification of lipid profiles even in patients with normal cholesterol levels, as well as anti-inflammatory actions and other properties not directly related to lipid lowering. [24][25][26][27] These mechanisms by which statins make plaques less vulnerable are not well understood. Intravascular ultrasound can now delineate statin-induced changes in plaque constituents.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] These benefits appear to derive largely from a stabilizing effect on high-risk atherosclerotic plaques through modification of lipid profiles as well as other properties not directly related to lipid lowering. [24][25][26][27] The purpose of this study was to assess the effect of statins on expression of CRP, interleukin-6 (IL-6), adhesion molecules, and anti-oxLDL Ab in patients with unstable angina undergoing coronary stenting.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence to suggest that statins have pleiotropic effects that help to stabilize vulnerable atherosclerotic plaques [6,7]. These include improved endothelial function and vasomotion, antiproliferative and anti-inflammatory actions, and diminished platelet reactivity and thrombogenicity.…”
Section: Opinion Statementmentioning
confidence: 99%